Population dynamics of mycoflora and incidence of black point disease in wheat grains - Malaker, PK; Mian, IH (Bangladesh Journal of Agricultural Research, 2010)
An attempt was made to monitor the prevalence of different fungi associated with floret lemma and developing grains of wheat and to assess the subsequent incidence of black point disease under different exposure periods of the spikes to airborne inocula of the causal fungi. Altogether 16 fungi representing 11 genera were detected from lemma and developing grains. The predominant fungi, in order of prevalence, were A. alternata, B. sorokiniana, C. cladosporioides, C. lunata, Fusarium spp. and E. purpurascens. Other fungi occurring less commonly were A. triticina, C. pallescens, Nigrospora sp., Phoma sp., Chaetomium sp., B. tetramera, B. oryzae, Aspergillus flavus, A. niger and Doratomyces sp. The incidence of all the fungi except Fusarium spp. was higher in lemma than in grains. In lemma, A. alternata occurred with the highest frequency, while the incidence of B. sorokiniana was found highest in grains. The population of A. alternata, B. sorokiniana, C. lunata, E. purpurascens and Fusarium spp. increased with the age of lemma and developing grains whereas the incidence of C. cladosporioides increased at early stages but declined at later stages of grain development. Other fungi did not follow any definite pattern in their incidence during grain development. The occurrence of black pointed grains per spike, percent black pointed grains and black point index were found increasing with the increase in exposure period of the spikes to airborne inocula of the causal fungi. Keywords: Mycoflora; black point; wheat. DOI: 10.3329/bjar.v35i1.5861 Bangladesh J. Agril. Res. 35(1) : 1-10, March 2010